Factors associated with excessive daytime sleepiness among Brazilian adolescents - Meyer C.* (2019)
© 2019, © 2019 Taylor & Francis Group, LLC.This study aimed to verify the prevalence and factors associated with excessive daytime sleepiness (EDS) among adolescents. In all, 1.132 people participated. They were aged between 14 and 19 years, of both sexes and they came from a city in southern Brazil. Many socio-demographic variables were collected (sex, age group, socioeconomic status, period of study, year of school and work), also variables related to their health (level of physical activity, alcohol intake, smoking, misuse of medicines, stress control, duration of sleep, sedentary behavior and self-rated health) and EDS, through the Pediatric Daytime Sleepiness Scale (PDSS). The prevalence of EDS in general sample was 54.2% and average score in PDSS was 16.0 (5.7). Comparing results between both sexes, female sex presents the higher prevalence of EDS (64.3%) and greatest average PDSS score 17.5 (5.4) compared to male sex (35.7%) with 14.5 (5.6%) score (p <.001). In analysis of the prevalence ratio, using 15 as an EDS cut-off point, prevalence was 35% higher in the female sex (PR = 1.35 CI 95% 1.08–1.69, p =.010). In addition, adolescents which had lower self-rated health (PR = 1.24 CI 95% 1.01–1.52, p =.038), low stress control (PR = 1.28 CI 95% 1.05–1.57, p =.014) and short sleep duration (PR = 1.30 CI 95% 1.02–1.65, p =.029), presented higher prevalence of EDS. High prevalence of EDS was identified, being more common in young women. Adequate sleep, greater stress control and better health perception should be promoted among Brazilian adolescents.